Pengaruh Ice Breaking Terhadap Motivasi Belajar Siswa Kelas IV pada Mata Pelajaran Muatan Lokal: Bahasa Simalungun di UPTD SDN 122401 Kota Pematangsiantar - Saragih, Ulva Maryani; Betty Simanjuntak, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Through a preliminary study on students' motivation levels toward the Simalungun local content subject, it was found that the motivation level of students towards the Local Content Subject (Simalungun Language) was relatively low. The aim of this research is to determine the influence of icebreaking on students' motivation levels in the local content subject (Simalungun Language) at UPTD SDN 122401 in the city of Pematangsiantar. This research is quantitative in nature, and the method employed is an experimental method with the research design of